Pendekatan Ilmu Sosial Profetik Dalam Memahami Makna Ayat-Ayat Al-Qur’an - Irwanto Irwanto (LITERASI (Jurnal Ilmu Pendidikan), 2014)
Al-Quran as paradigm is the concepts that the moslems were able to make the Qur'an did construction of knowledge that allows us to understand the reality referred to the Qur'an itself. This means that the Qur'an construct knowledge which provides the basic for the action. It is allowing construction to construct a system, including system science. Thus Qur'an provided both an overview axiological and epistemological insight. In the islamic studies approach, a lot of methods that can be used as an analytical strategy to dissect the intricacies of Islam. One method that can be used is the prophetic social science approach. It was used to understand the meaning of the writer verses of the Qur'an. It was conceived and developed by Kuntowijoyo. This approach is more focused on aspects of empirical, historical, and temporal. Thus, it would be open the possibility of review, revision and reconstruction that may be present at any time and keep it to a text which became the study.